The Satisfaction Rate of Clients of Urban Health Centers from the Service Delivery System - Rahil Ghorbani Nia; Atefe Morsalpor (Kerman University of Medical Sciences, 2018)
The Satisfaction Rate of Clients of Urban Health Centers from the Service Delivery System   Ghorbani Nia Rahil1*, Morsalpoor Atefe2   1. Ph.D Student of Health Care Management, School of Health Management and Information Sciences, Kerman University of Medical Sciences, Kerman, Iran 2. BSc Student of Health Care Services Management, Deparment of Health Care Services Management, School of  Public Health, Bam University of Medical Sciences, Bam, Iran *Correspondence: Future Studies Institute of Health, Campus of  Kerman University of Medical Sciences, Haft Bagh Alavi Blvd., Kerman, Iran Tel: 00983431325403                                             Email: r.ghorbani6790@gmail.com Abstract: Background & Objectives: An effective health system can only fulfill its mission, which is providing community health, through providing desirable services; this is possible through the services of health centers. The aim of this study was to find the satisfaction rate of people referred to urban health centers of Bam/ Iran. Methods: This descriptive-analytic study was conducted on 447 clients referred to Bam urban health centers from May 2015 to June 2016 for receiving outpatient services. Data collection tool was a 26-item questionnaire for the satisfaction of clients of urban health centers. Data were analyzed through SPSS20 and using t-test and Kruskal-Wallis statistical tests. Results: The majority of the study subjects were female, had a university degree, with more than 2 visits. In all aspects, the subjects expressed a high degree of satisfaction. The satisfaction rate showed significant relationship with the variables of education, number of visits, the reason for referral, occupation, but not with age.  Conclusion: Overall, the performance of the centers seems to have been successful and by upgrading some of the processes, they can get a higher level of satisfaction. Also, given the principle of continuous improvement, it is necessary to plan appropriately to maintain and improve the existing conditions.   Keywords: Satisfaction, Urban Healthcare Services Centers, Healthcare Services, Ambulatory Care, Patients   Citation: Ghorbani Nia R, Morsalpoor A. The Satisfaction Rate of Clients of Urban Health Centers from the Service Delivery System. Journal of Health Based Research 2018; 4(3): 233-44. [In Persian]